PEMANFAATAN ABU DASAR INSINERATOR SEBAGAI BAHAN BANGUNAN - Wilda Khairuna; Suhendrayatna .; Muhammad Zaki (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
This research is purposed to study the mixture ratio that can be used to produce mortar which meets SNI standard, by substituting a part of sand with bottom ash collected from RSUD Dr.Zainoel Abidin incinerator in the mixture. The mixture planning was done according to practical instruction ASTM C 305, and compressive strenght test on the mortar produced was performed. The mixture ratio of cement: sand: ash that was used was 1:3:1, 1:2:2, and 1:1:3. The testing materials were 63 cubes with dimension 5 cm × 5 cm × 5 cm. The compressive strenght test  result after 28 days of mortar curing time showed that the mortar in every mixture ratio has met SNI 03-6882-2002, which is a specification of mortar for masonry work. The highest result of compressive strenght test is 18.71 MPa, which was obtained from mixture ratio 1:3:1, with addition of incinerator bootom ash by 25% of volume of sand used, but the value was decreasing as the increasing amount of incinerator bottom ash added in the mixture. The result of compression test on mortar with incinerator bottom ash addition was bigger and characteristically seemed more compact compared to mortar without ash.